Versatile Use of Rhomboid Flaps for Closure of Skin Defects - Ensar Zafer Barin; Selma Denktas Kuduban; Hakan Cinal; Said Algan; Onder Tan; Osman Enver Aydin (Eurasian Journal of Medicine, 2011)
Objective: The aim of this study is to present our clinical experience with rhomboid flaps.Materials and Methods: Twenty-four patients who were operated on between January 2006 and October 2010 were included in the study. All defects were reconstructed using rhomboid flaps.Results: Twenty-four patients were operated on for various reasons, and 26 rhomboid flaps were performed. Eleven of the 24 cases were male, and the median age of participants was 47.5 years. Eight cases were operated on under general anesthesia, and 13 were locally anesthetized; the remaining cases were operated on under regional anesthesia. In 17 cases, the defect was due to a benign or malignant tumor excision, and five cases were operated on due to burn contracture. There were no occurrences of partial or total flap necrosis or hematoma in our series. Conclusion: Our series indicates that rhomboid flaps can be safely used to reconstruct small to moderately sized skin defects.